Urdu Ethics Literature in Colonial India Akhlāq in the Vernacular - Muhammad Irfan Haider (بازیافت)
Akhlaq is a classical genre of Islamic literature that focuses on ethical conduct and self-cultivation. The article argues that Urdu akhlaq literature offers a fresh perspective on the history of Islam in colonial India by highlighting a popular and non-institutional form of Islamic knowledge production. Traditionally, studies of Islamic thought in colonial India have focused on elite figures and institutions. Urdu akhlaq literature, produced for a literate but not necessarily elite audience, provides insights into popular Muslim concerns during this period. Urdu akhlaq texts demonstrate the adaptability of the akhlaq genre. While drawing on its Islamic philosophical heritage, these texts also incorporate knowledge from diverse sources, including Greek philosophy, Hinduism, and even European thinkers.This inclusion suggests that Islamic and colonial knowledge production were not separate entities in late-colonial India. Rather, they interacted and influenced each other within the context of popular print culture. Translation of this article in Urdu can lead to familiarity with a new perspective. The translator has added numerous footnotes and annotations.